(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2012)
This article focuses on the amendments passed in 2012 on the Housing Development Act and Perumahan Rakyat 1 Malaysia Act 2012, which were both gazetted on the 9th February 2012. The article aims to analyse and present the current legal issues. The research method employed is qualitative. The discussions and issues raised endeavour to facilitate an awareness and understanding of the latest amendments to the Housing Development Act, and whether those admendment s are able to offer better protection to the house buyers. Keywords: housing law, low-cost houses, medium-cost houses, housing developer, housing development